2018
DOI: 10.1016/j.idairyj.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of protein standardisation media and heat treatment on viscosity and related physicochemical properties of skim milk concentrate

Abstract: Influence of protein standardisation media and heat treatment on viscosity and related physicochemical properties of skim milk concentrate,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…All formulas were found to be shear thinning at PD, with formulas containing 18 g/100 g protein having the highest viscosity on shearing at 300 s -1 (Figure 1). In the present study, as protein:lactose ratio increased, the viscosity of the formulas increased and it has previously been demonstrated that dairy concentrates with higher lactose contents have lower viscosity than those with higher protein contents (Westergaard 2004;Schuck et al 2005;Murphy et al 2018).…”
Section: Viscosity Of Model Formulas In-processsupporting
confidence: 55%
“…All formulas were found to be shear thinning at PD, with formulas containing 18 g/100 g protein having the highest viscosity on shearing at 300 s -1 (Figure 1). In the present study, as protein:lactose ratio increased, the viscosity of the formulas increased and it has previously been demonstrated that dairy concentrates with higher lactose contents have lower viscosity than those with higher protein contents (Westergaard 2004;Schuck et al 2005;Murphy et al 2018).…”
Section: Viscosity Of Model Formulas In-processsupporting
confidence: 55%
“…However, the β‐lg band was almost completely absent in HHSMC samples (120°C for 60 s) and a reduction in the α‐lactalbumin band (denoted by a in Figure 2b) was also observed in comparison with the other heat‐treated samples, demonstrating heat‐induced protein–protein interactions (Murphy et al . 2018). In addition, an increase in the band intensity of aggregated protein (denoted by b in Figure 2b) in HHSMC was also observed.…”
Section: Resultsmentioning
confidence: 99%
“…The protein profiles of SMC samples were determined using pre‐cast sodium dodecyl sulphate–polyacrylamide gel electrophoresis (SDS‐PAGE; Novex Technologies, Thermo Fisher Scientific, Dublin, Ireland) under reducing and nonreducing conditions using the method described by Murphy et al . (2018). After electrophoresis, the gels were stained overnight using 0.05% (w/v) Coomassie brilliant blue R‐250 in 25% (v/v) isopropanol and 10% (v/v) acetic acid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ashed samples were first dissolved in 1 ​mL of 1 ​M nitric acid and subsequently diluted 10 4 -fold with 2 ​mM nitric acid. The resulting solutions were filtered using 0.2 ​μm polysulfone syringe filters before analysis, and their mineral content was determined as described previously ( Murphy et al., 2018 ), using a Dionex ICS-5000+ Ion Chromatography system (Thermo Fischer Scientific, Dublin, Ireland). Cations were separated using a CS16-4 ​mm column under isocratic conditions with methanesulfonic acid used for eluent generation, and anions were separated using an AS11-HC column under gradient conditions, with KOH used for eluent generation.…”
Section: Methodsmentioning
confidence: 99%